The little book of hygge eaudiobook Danish secrets to happy living. - Wiking, Meik (2017)
Embrace Hygge (pronounced hoo-ga) and become happier with this definitive guide to the Danish philosophy of comfort, togetherness, and well-being. Why are Danes the happiest people in the world? The answer, says Meik Wiking, CEO of the Happiness Research Institute in Copenhagen, is Hygge. Loosely translated, Hygge—pronounced Hoo-ga—is a sense of comfort, togetherness, and well-being. ""Hygge is about an atmosphere and an experience,"" Wiking explains. ""It is about being with the people we love. A feeling of home. A feeling that we are safe."" Hygge is the sensation you get when you're cuddled up on a sofa, in cozy socks under a soft throw, during a storm. It's that feeling when you're sharing comfort food and easy conversation with loved ones at a candlelit table. It is the warmth of morning light shining just right on a crisp blue-sky day. The Little Book of Hygge introduces you to this cornerstone of Danish life, and offers advice and ideas on incorporating it into your own life, such as: Get comfy. Take a break. Be here now. Turn off the phones. Turn down the lights. Bring out the candles. Build relationships. Spend time with your tribe. Give yourself a break from the demands of healthy living. Cake is most definitely Hygge. Live life today, like there is no coffee tomorrow. From picking the right lighting to organizing a Hygge get-together to dressing hygge, Wiking shows you how to experience more joy and contentment the Danish way.